Exploring the Value of Ethical Values as a Pillar of Law Enforcement with Integrity at the Kolaka District Attorney’s Office - Basrawi Basrawi; Yulianda Yulianda; Hasrianti Hasrianti; Andi Sri Ulan; Munarti Munarti (Sangia Nibandera Law Research, 2025)
This study aims to analyze the implementation of professional ethics in the Kolaka District Attorney's Office and its impact on the integrity and public trust in law enforcement institutions. Using an empirical legal approach, data were collected through interviews with prosecutors, direct observation, and documentation studies related to the code of ethics regulated in the Regulation of the Attorney General of the Republic of Indonesia Number PER-014/A/JA/11/2012. The results of the study indicate that despite consistent efforts to implement the code of ethics, violations such as abuse of authority and non-compliance with ethical norms are still found. These violations have a negative impact on the image of the prosecutor's office and reduce public trust in the justice system. Therefore, it is necessary to increase ethics training, strict supervision, and feedback mechanisms from the public to ensure integrity in the implementation of prosecutors' duties in order to realize justice.